Behaviors Influencing Human Immunodeficiency Virus Transmission in the Context of Positive Prevention among People Living with HIV/Acquired Immunodeficiency Syndrome in Iran: A Qualitative Study - Radfar, Seyed Ramin (Int J Prev Med, 2014)
BACKGROUND: Identifying factors, which influence health behaviors is critical to designing appropriate and effective preventive programs. Human immunodeficiency virus (HIV) transmission is highly related to people behaviors and understanding factors influencing healthy behaviors among Iranian people living with HIVs (PLHIVs)/acquired immunodeficiency syndrome (AIDS) is very important to tailor an effective response to HIV/AIDS epidemic. METHODS: This study was conducted as a qualitative study by methods of focus group discussion and in-depth interview in six provinces of Iran with 64 PLHIVs to determine factors influence engagement in positive prevention. RESULTS: Knowledge and education, feelings of responsibility and positive prevention practices were identified as the primary domains of engagement. These domains were found to be influenced by feelings of ostracism and frustration, poverty, barriers to disclosure of HIV status, access to and utilization of drug abuse treatment services and antiretroviral therapy, adherence to treatment, age, religiousness, sex work, singleness, and incarceration. CONCLUSIONS: Designing new interventions and updating current interventions directed toward the aforementioned factors should be addressed by responsible Iranian authorities in order to have a national effective response on the HIV/AIDS epidemic.